2017
DOI: 10.1371/journal.pone.0174334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UVB radiation on grazing of two cladocerans from high-altitude Andean lakes

Abstract: Climate change and water extraction may result in increased exposition of the biota to ultraviolet-B radiation (UVB) in high-altitude Andean lakes. Although exposition to lethal doses in these lakes is unlikely, sub-lethal UVB doses may have strong impacts in key compartments such as zooplankton. Here, we aimed at determining the effect of sub-lethal UVB doses on filtration rates of two cladoceran species (Daphnia pulicaria and Ceriodaphnia dubia). We firstly estimated the Incipient Limiting Concentration (ILC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Thus, any factor that potentially damages zooplankton may affect the whole ecosystem via trophic interactions (Häder, Helbling, Williamson, & Worrest, ; Häder et al., ; Rautio & Tartarotti, ). Additionally, it has been suggested that interactions between species with different tolerance to UVR may also alter the dynamics and structure of the ecosystem (Fernández & Rejas, ; Hansson, ; Sommaruga, ). Two groups of strategies could influence the zooplankton tolerance to UVR: The first involves avoiding or preventing the damage, either behaviorally (through vertical migration, Hylander & Hansson, ; Kessler, Lockwood, Williamson, & Saros, ) or physiologically (through photo‐protective compounds as melanin or carotenes, Rautio, Bonilla, & Vincent, ; Rautio & Korhola, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any factor that potentially damages zooplankton may affect the whole ecosystem via trophic interactions (Häder, Helbling, Williamson, & Worrest, ; Häder et al., ; Rautio & Tartarotti, ). Additionally, it has been suggested that interactions between species with different tolerance to UVR may also alter the dynamics and structure of the ecosystem (Fernández & Rejas, ; Hansson, ; Sommaruga, ). Two groups of strategies could influence the zooplankton tolerance to UVR: The first involves avoiding or preventing the damage, either behaviorally (through vertical migration, Hylander & Hansson, ; Kessler, Lockwood, Williamson, & Saros, ) or physiologically (through photo‐protective compounds as melanin or carotenes, Rautio, Bonilla, & Vincent, ; Rautio & Korhola, ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, it has been well demonstrated that nature ultraviolet-B (UV-B) radiation increased signi cantly with the continuing depletion of stratospherico zone, which has becoming one of the grave concerns and most striking global changes [10,11]. There is growing evidence that adverse biological effects of ambient ultraviolet radiation exposure occur in not only marine but also freshwater ecosystem at different trophic levels [11,12], involving algae [13], rotifers [14,15], copepods [16,17], cladocerans [18], shrimps [19,20] and shes [21]. In all cases, UVR was found to harm the organisms in question by damaging DNA directly at the molecular level and affect tness at the individual and population levels [22].…”
mentioning
confidence: 99%
“…35, e13 dominance of taxa with small body size. Added to this, the low tolerance that filter cladocerans with longer body lengths have to UV radiation, as reported in some studies (De Los Ríos, 2005;Fernández & Rejas, 2017) could also explain the small effect zooplankton grazing has on phytoplankton in tropical and subtropical ecosystems. In these environments, underwater radiation is more intense than in temperate environments, which compromises the grazing rate of organisms such as Daphnia (Fernández & Rejas, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, species with a larger body can monopolize resources, excluding smaller species. These species are also more efficient grazers and have a greater impact on energy transfer in aquatic ecosystems (Fernández & Rejas, 2017). In August, the contribution of Daphnia to the biomass decreased, probably opening a niche space, which was occupied by opportunistic rotifers (G3, G4, G5, and G6), contributing to the increased grazing potential of these groups.…”
Section: Discussionmentioning
confidence: 99%